2005
DOI: 10.1097/01.mib.0000160803.44449.a5
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Efficacy in Pediatric Ulcerative Colitis

Abstract: Infliximab should be considered in the treatment of children with symptoms of acute moderate to severe ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 36 publications
1
39
0
1
Order By: Relevance
“…5 Published experience with infliximab in pediatric disease is increasing, but there are still a significant number of children who do not respond to this medication (Table 4). [22][23][24][25][26] Cyclosporine is effective in adults with colitis, 27 but usually is given intravenously, requires careful monitoring, and has unpleasant side effects such as hirsutism and gingival hyperplasia. 28 Tacrolimus offers several advantages for children, including oral administration and fewer cosmetic side effects than cyclosporine.…”
Section: Discussionmentioning
confidence: 99%
“…5 Published experience with infliximab in pediatric disease is increasing, but there are still a significant number of children who do not respond to this medication (Table 4). [22][23][24][25][26] Cyclosporine is effective in adults with colitis, 27 but usually is given intravenously, requires careful monitoring, and has unpleasant side effects such as hirsutism and gingival hyperplasia. 28 Tacrolimus offers several advantages for children, including oral administration and fewer cosmetic side effects than cyclosporine.…”
Section: Discussionmentioning
confidence: 99%
“…Eidelwein et al 35 showed an initial short-term response to infliximab in pediatric UC: 75% had complete resolution of symptoms, and 25% improved after initial infusion; many of these patients continued to respond in the subsequent 6 months, but one-third of children underwent colectomy. The authors concluded that infliximab is a valid alternative therapy to cyclosporine or colectomy in patients requiring chronic CS therapy or not responding to 6-MP or azathioprine.…”
Section: Infl Iximabmentioning
confidence: 99%
“…Surgery is unavoidable in these patients, and time delay in nonresponders to medical therapy is associated with an increased risk of postoperative complications. 35 Indications for surgery, other than ASC, include toxic megacolon, perforation, severe hemorrhage, or significant clinical deterioration during medical therapy. Although in general, medical rescue therapy should be considered as first-line treatment in steroid-refractory ASC, colectomy is still a cornerstone of any proposed management algorithm.…”
Section: Surgery and A Time-limited Approachmentioning
confidence: 99%
“…Hierfür spricht auch eine retrospektive Studie von Eidelwein et al [9], die allerdings nur wenige Patienten einschloss. 12 Colitis-ulcerosa-Patienten erhielten IFX, 3 mit fulminantem Verlauf, 3 mit akuter Exazerbation, 5 mit Steroidabhängig-keit und einer mit steroidrefraktärer Colitis ulcerosa.…”
Section: Colitis Ulcerosaunclassified